Cerebral blood flow and its connectivity features of auditory verbal hallucinations in schizophrenia: A perfusion study. (28th February 2017) - Cui, Long-Biao; Chen, Gang; Xu, Zi-Liang; Liu, Lin; Wang, Hua-Ning; Guo, Li; Liu, Wen-Ming; Liu, Ting-Ting; Qi, Shun; Liu, Kang; Qin, Wei; Sun, Jin-Bo; et al.
Abstract: The goal of the study was to investigate cerebral blood flow (CBF) and its connectivity (an across-subject covariance measure) patterns of schizophrenia (SZ) patients with auditory verbal hallucinations (AVHs). A total of demographically matched 25 SZ patients with AVHs, 25 without AVHs, and 25 healthy controls (HCs) underwent resting state perfusion imaging using a pulsed arterial spin labeling sequence. CBF and its connectivity were analyzed and then CBF topological properties were calculated. AVHs patients exhibited decreased CBF in the bilateral superior and middle frontal gyri and postcentral gyri, and right supplementary motor area compared with SZ patients without AVHs. SZ patients without AVHs showed reduced CBF in the left middle frontal gyrus relative to HCs. Moreover, AVHs groups showed distinct connectivity pattern, an intermediate level between HCs and patients without AVHs in the global efficiency. Our study demonstrates aberrant CBF in the brain regions associated with inner speech monitoring and language processing in SZ patients with AVHs. The complex network measures showed by CBF-derived functional connectivity indicate dysconnectivity between different functional units within the network of AVHs in SZ. Our findings might shed light on the neural underpinnings behind AVHs in this devastating disease at the level of CBF and its connectivity. Highlights: AVHs in SZ show dysfunction of the regions involving speech imagery, production, and monitoring. SZ patients with AVHs showed deficit communication within the brain network. CBF values help to discriminate SZ patients with AVHs from those without AVHs. CBF measure might be an effective indicator of AVHs vulnerability in SZ patients.